1997
DOI: 10.1021/bi9620060
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the vnd/NK-2 Homeodomain with DNA by Nuclear Magnetic Resonance Spectroscopy:  Basis of Binding Specificity

Abstract: The interactions responsible for the nucleotide sequence-specific binding of the vnd/NK-2 homeodomain of Drosophila melanogaster to its consensus DNA binding site have been identified. A three-dimensional structure of the vnd/NK-2 homeodomain-DNA complex is presented, with emphasis on the structure of regions of observed protein-DNA contacts. This structure is based on protein-DNA distance restraints derived from NMR data, along with homology modeling, solvated molecular dynamics, and results from methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 40 publications
4
85
0
1
Order By: Relevance
“…The NMR studies have demonstrated that position 54 makes important contacts with the DNA, and these contacts have been shown to be critical to recognition of the unusual sequence of DNA (13,33). Replacement of the tyrosine with methionine alters the strengths of the interactions with the various neighboring DNA bases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NMR studies have demonstrated that position 54 makes important contacts with the DNA, and these contacts have been shown to be critical to recognition of the unusual sequence of DNA (13,33). Replacement of the tyrosine with methionine alters the strengths of the interactions with the various neighboring DNA bases.…”
Section: Resultsmentioning
confidence: 99%
“…Within the NK family of homeobox genes, the NK-2 class, whose founding member is vnd͞NK-2 from Drosophila melanogaster (8)(9)(10), is defined by the presence of tyrosine in position 54 of the homeodomain (11,12). This tyrosine is the major determinant of the nucleotide-binding specificity (13,14) to a sequence of DNA that contains 5Ј-CAAGTG-3Ј as its core (15)(16)(17)(18) through direct interaction between the side chain of Y54 and the cytosine that complements the guanine (in bold) of the consensus DNA (14). This core DNA sequence is recognized by all members of the Nirenberg and Kim (NK)-2 class of homeodomains (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…The sequence of the NKX2-1 homeodomain (HD) (161-227) was subjected to a Blast search (http://blast.wustl.edu) using the Brookhaven Protein Data Bank (http://www.rcsb.org/index.html) as the database. This search resulted in several NMR structures, two of which were used in this study: the structure of rat Nkx2-1 HD (PDB code 1FTT [Esposito et al, 1996]) and the structure of drosophila vnd/nk2 HD in complex with a DNA fragment of 16 nucleic acids on each strand (PDB code 1NK2 [Gruschus et al, 1997]). This choice was governed by a sequence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Double-stranded oligonucleotides that bind to vnd͞NK-2 HD protein were purified by a modification of the method of Ekker et al (36). A library of oligonucleotides, 64 nucleotide residues in length, was synthesized that contained a variable central region consisting of random sequences, 16 nucleotide residues in length, and constant 5Ј and 3Ј regions that contained a ClaI and an EcoRI site, respectively, as follows: (ϩ)5Ј-ACGTTAG-CATCGATGTACCTGTCG(N) 16 CCTGTCAGGAATTCTAG-CTGGCAT-3Ј. Complimentary oligonucleotide strands were synthesized and labeled by extension of primer R22 [(Ϫ)5Ј-ATGCCAGCTAGAATTCCTGACA-3Ј] in the presence of [␣-32 P]dATP and three unlabeled deoxynucleoside triphosphates catalyzed by the Klenow enzyme.…”
Section: Purification Of Oligonucleotides Binding To Vnd͞nk-2 Hd Protmentioning
confidence: 99%
“…Regulation of vnd͞NK-2 expression is required for both neural and glial specification (13). The three-dimensional structure of the vnd͞NK-2 HD and its interaction with a target oligodeoxynucleotide (oligonucleotide) have been reported (14)(15)(16)(17). Site mutations (single, double, or triple sites) involving Tyr-54 (Y54M) all showed a decrease of one order of magnitude in their binding affinities to the vnd͞NK-2 consensus DNA binding site (18).…”
mentioning
confidence: 99%